Incidence of depression in patients with psoriasis and psoriatic arthritis treated with biologic therapy: Protocol for a systematic review and meta-analysis - Emily Sirotich; Weston Lowry; Shi-Yi Wang; Madison Jurgens; Jeffrey M. Cohen (PLoS ONE, 2026)
Background Psoriasis and psoriatic arthritis are chronic immune-mediated diseases with both physical and psychological consequences. Depression is a common comorbidity associated with impaired quality of life and lower treatment adherence. Biologics, monoclonal antibodies targeting key cytokines, may favorably influence depressive symptoms by reducing systemic inflammation and improving disease activity. However, current evidence is heterogeneous and has not been comprehensively synthesized. Methods This systematic review and meta-analysis will evaluate whether biologic therapy reduces the risk of depression among adults with psoriasis or psoriatic arthritis compared with non-biologic treatment or no therapy. Electronic searches will include MEDLINE, Embase, Cochrane Library, PsycINFO, and ClinicalTrials.gov. Eligible designs are randomized controlled trials (RCTs), cohort, and case–control studies reporting depression incidence or prevalence. Depression may be ascertained through clinical diagnosis or validated instruments. Study selection, data extraction, and risk-of-bias assessment will be performed independently by two reviewers. Using the Cochrane Risk of Bias 2.0 tool and the Newcastle–Ottawa Scale, we will assess quality of each study. Data permitting, random-effects meta-analysis will estimate pooled risk ratios (RRs) or odds ratios (ORs) with 95% confidence intervals (CIs). Certainty of evidence will be rated using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. Discussion This review will synthesize the impact of biologic therapy on incident depression in psoriasis and psoriatic arthritis, informing integrated care for patients with psoriatic disease. Systematic review registration PROSPERO (submitted; registration number to be confirmed prior to data extraction).